A Note on Closed-Form Representation of Fibonacci Numbers Using Fibonacci Trees. (12th February 2014) - Raman, Indhumathi
Abstract : We give a new representation of the Fibonacci numbers. This is achieved using Fibonacci trees. With the help of this representation, the n th Fibonacci number can be calculated without having any knowledge about the previous Fibonacci numbers.